Workplace Diversity and Intraindividual Identity Conflict: Implications for Stress in Non-Profit Organizations - Berrios-Espinoza, R; Calderon-Orellana, M (SAGE PUBLICATIONS INC, 2025)
This study investigates the relationship between workplace diversity and intraindividual identity conflict, on its impact on employee stress within Chilean non-profit organizations. Using a quantitative methodology, data were collected from 173 participants through a two-phase assessment. The findings indicate a positive association between gender diversity and intraindividual identity conflict, while racial diversity is negatively associated with such conflict. Moreover, intraindividual identity conflict was significantly correlated with higher stress levels among employees. These results provide new insights into the dynamic interplay between diversity and identity, showing that while some dimensions of diversity may exacerbate identity conflict, others can mitigate it. This study underscores diversity as a complex, double-edged process affecting both individual well-being and organizational dynamics, emphasizing its role in stress within highly demanding occupations such as non-profit organizations.